2022
DOI: 10.3389/fimmu.2021.783806
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Mitigates Oxazolone-Induced Colitis in Microbiota-Dependent Manner

Abstract: Levels of type 2 cytokines are elevated in the blood and intestinal tissues of ulcerative colitis (UC) patients in the active phase; this phenomenon indicates the participation of type 2 immune response in UC progression. The beneficial effects of melatonin in dextran sodium sulfate (DSS) and 2,4,6-trinitrobenzene sulfonic acid (TNBS) colitis models have been illustrated, but its role in the oxazolone (Oxa)-induced colitis model (driven by type 2 immune response) remains relatively unknown. We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 62 publications
(73 reference statements)
3
20
1
1
Order By: Relevance
“…It suggested that melatonin may strengthen the tight connection between cells, regulate intestinal permeability, repair and maintain the stability of intestinal mechanical barrier, which effectively prevent toxins and other bacterial metabolites in the intestine from entering the blood and cause cascading chain inflammatory reaction. A similar effect was also observed in the oxazolone induced colitis model ( Zhao et al, 2021 ), indicating that melatonin’s preservation of the intestinal barrier was not confined to stress damage and that its barrier protective role had a broader application. In addition, melatonin accelerates the emptying effect of the gastrointestinal tract in mice after SCI ( Jing et al, 2019 ), demonstrating that melatonin enhances gastrointestinal function, promotes peristalsis and strengthens the mechanical barrier.…”
Section: The Relationship Between Melatonin and Intestinal Microbiotasupporting
confidence: 60%
See 2 more Smart Citations
“…It suggested that melatonin may strengthen the tight connection between cells, regulate intestinal permeability, repair and maintain the stability of intestinal mechanical barrier, which effectively prevent toxins and other bacterial metabolites in the intestine from entering the blood and cause cascading chain inflammatory reaction. A similar effect was also observed in the oxazolone induced colitis model ( Zhao et al, 2021 ), indicating that melatonin’s preservation of the intestinal barrier was not confined to stress damage and that its barrier protective role had a broader application. In addition, melatonin accelerates the emptying effect of the gastrointestinal tract in mice after SCI ( Jing et al, 2019 ), demonstrating that melatonin enhances gastrointestinal function, promotes peristalsis and strengthens the mechanical barrier.…”
Section: The Relationship Between Melatonin and Intestinal Microbiotasupporting
confidence: 60%
“…In addition, melatonin enhances the abundance of bacteria and decrease the ratio of firmicum to Bacteroides in a high-fat diet-induced obesity mouse model ( Xu P. et al, 2017 ; Yin et al, 2018 ). In the ochratoxina induced liver injury model, melatonin increase the abundance of Bacteroides, verrucous microorganisms and actinomycetes, while decrease the abundance of firmicum and Lactobacillus ( Zhang H. et al, 2021 ; Zhao et al, 2021 ). In terms of microbial metabolism, melatonin significantly reduces the relative abundance of the microbiome in the cysteine and methionine metabolism and peptidoglycan biosynthesis pathway in the restraint stress mouse model, while increasing the relative abundance of the microbiome in the tryptophan metabolism, aminobenzoic acid degradation, renin angiotensin system, γ-aminobutyric acid ergic synapses and type II diabetes pathway ( Lin et al, 2021 ).…”
Section: The Relationship Between Melatonin and Intestinal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, in animal colitis models, MT increased bacterial richness and diversity in the gut [ 135 , 136 ]. This finding might have a translational impact, as a decrease in these parameters strongly correlates with IBD [ 140 , 141 ].…”
Section: Melatonin Involvement In Dysbiosis-associated Conditions Via...mentioning
confidence: 99%
“…Melatonin is synthesized in the enterochromaffin (EC) cells throughout the gut, and deficiencies in melatonin have been linked to increased permeability of the gut, increasingly associated with a range of diseases ( 135 , 136 ). A recent study conducted by Zhao et al demonstrated that melatonin reverses Oxazolone-induced colitis by suppressing type 2 immune response and attenuating intestinal permeability and neutrophil infiltration ( 137 ). Melatonin's role in treating intestinal co-morbidities associated with OUD and SARS-CoV-2 infection should be further explored.…”
Section: Melatonin Therapy For Sars-cov-2 Infection and Oudmentioning
confidence: 99%